Context, Challenges, and Prospects for Agricultural Extension in Nigeria - Nina Camillone; Sjoerd Duiker; Mary Ann Bruns; Johnson Onyibe; Akinwumi Omotayo (Journal of International Agricultural and Extension Education, 2020)
Agricultural extension programs have been implemented in Nigeria by governmental and non-governmental agencies from the colonial era to the present day as a means toward bolstering economic development, rural livelihoods, food security, and trade relations. Nevertheless, funding and staffing levels in agricultural extension remain low compared to Nigeria’s farming population. With a brief review of past initiatives, current challenges, and potential opportunities, this article gives recommendations in three focus areas for maximizing the effectiveness of Nigerian agricultural extension: (1) prioritize human education over input provisioning in the definition of agricultural extension’s primary purpose; (2) aim for household food security, not solely business expansion, to ensure the inclusion of the most vulnerable farmers; and (3) foster multidirectional communication among academic researchers, extension agents, and farmers. Overall, this article argues that taking a farmer-centric educational approach to agricultural extension, rather than a farm-centric business approach, will have the most profound and sustained impact on Nigerian agricultural development.
Keywords: Nigeria; agricultural extension; rural development; fertilizer subsidies; farmer education; household food security; agribusiness; research-farmer linkage